2017
DOI: 10.1002/biot.201700402
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Quantum Dots Steer and Detach Microtubules From Kinesin‐Coated Surfaces

Abstract: The microtubule (MT)-kinesin system has been extensively studied because of its role in cellular processes, as well as its potential use for controllably transporting objects at the nanoscale. Thus, there is substantial interest in methods to evaluate MT properties, including bending radius and the binding energy of kinesin motor proteins to MT tracks. Current methods to identify these properties include optical tweezers, microfluidic devices, and magnetic fields. Here, the use of magnetic quantum dots (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previously, we have shown that magnetic forces on the order of 0.1-0.2 pN are required to capture similar nanocomposites 33,34 and that neodymium magnets can capture particles within B2 mm of their surfaces. 35 The absence of significant size change in the pellet or supernatant can be explained by structure stabilization engendered by strong van der Waals forces, dipole-dipole interactions between SPIONs, and entropic stabilization provided by the BCPs. These results indicate that magnetic forces applied after composite formation were not sufficient to break BCP entropic barriers to change composite size, at least at the strengths investigated here.…”
Section: Effect Of Magnetic Field Exposure After Spion Aggregate Synt...mentioning
confidence: 99%
“…Previously, we have shown that magnetic forces on the order of 0.1-0.2 pN are required to capture similar nanocomposites 33,34 and that neodymium magnets can capture particles within B2 mm of their surfaces. 35 The absence of significant size change in the pellet or supernatant can be explained by structure stabilization engendered by strong van der Waals forces, dipole-dipole interactions between SPIONs, and entropic stabilization provided by the BCPs. These results indicate that magnetic forces applied after composite formation were not sufficient to break BCP entropic barriers to change composite size, at least at the strengths investigated here.…”
Section: Effect Of Magnetic Field Exposure After Spion Aggregate Synt...mentioning
confidence: 99%
“…The gliding velocity is governed by the ATP concentration and temperature, , and the direction of the filament movement follows a persistent random walk driven by thermal fluctuations of the tip of the moving filaments . This persistent random walk, as well as the interaction of the filament with obstacles, can be simulated using Brownian dynamics methods. Gliding filaments can be confined by guiding structures to prescribed paths, , directed by obstacles, controlled by light, , or other stimuli, , and can capture analytes and carry cargo. , The natural arrangement of stationary filaments supporting the movement of biomolecular motors is also employed, but the transport distance is largely limited to the length of the filament or filament assembly in this geometry. These discoveries led to more advanced applications including sensors, computation, screens, and switches .…”
Section: Linear Biomolecular Motors Applicationsmentioning
confidence: 99%